Bioaccumulation of alkaline soil metals (Ca, Mg) and heavy metals (Cd, Ni, Pb) patterns expressed by freshwater species of Ulva (Wielkopolska, Poland) - Rybak, Andrzej; Messyasz, Beata; Łęska, Bogusława (WILEY-VCH Verlag GmbH & Co. KGaA, 2012)
The paper includes results of the first study on the accumulation of selected metals in freshwater populations of Ulva taxa at 16 sites in Poland. The thalli examined contained very high concentrations of Ca and Mg, owing to well-developed surface incrustations of carbonate. Among the heavy metals investigated, the most significant concentration in the thalli was Ni, whereas the lowest was Pb. The median concentrations of Ni and Cd in the freshwater Ulva thalli were significantly higher than those reported in the available literature for marine taxa of the same genus. Several statistically significant correlations were found when the concentrations of different metals in the thalli and the water were analysed.
Keywords: Ulva; Enteromorpha; Heavy metals; Freshwater; Macroalgae